Thermal Decomposition Kinetics and Mechanism of Lanthanide Nitrato Complexes of Pyridine-2-carboxaldehyde-4-aminoantipyrine and Dimethylsulfoxide - Sreeletha, G.S. (Asian Journal of Chemistry, 2016)
The thermal decomposition behaviour of lanthanide nitrato complexes of the Schiff base, pyridine-2-carboxaldehyde-4-aminoantipyrine (P2CA4AAP) and dimethylsulfoxide (DMSO), has been studied using TG and DTG analyses. The phenomenological and kinetics aspects of the TG curves are investigated for the evaluation of kinetic parameters such as activation energy, pre-exponential factor and entropy of activation using the Coats-Redfern equation. The rate controlling process obeys the ‘Mampel model’, representing random nucleation with one nucleus on each particle. There is no regular variation in the values of kinetic parameters for the decomposition of these complexes. The kinetic parameters indicate that the ligand is loosely bound to the metal ion and the activated complex is more ordered than the reactants.